Pinsip Kehati-hatian Pejabat Pembuat Akta Tanah Dalam Pengurusan Peralihan Tanah Letter C - Wanda, Hendry Dwicahyo; Sesung, Rusdianto (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Abstract: Land Acquisition Officer (PPAT) is often required to make the transfer of land right Letter C. As an official making an authentic deed, PPAT must have a precautionary attitude and good precision so that the deed made can guarantee the right of land for the community. In handling the land transfer of Letter C, PPAT needs to apply prudential principles in order to avoid problems in the future. PPAT should pay attention to the management in the kelurahan (officer in the level of village) associated with checking Letter C objects, documents related to the object, the identity of the parties, and permit applications. PPAT also needs to be careful in the management of the National Land Agency. The precautionary principles of PPAT are in need in order to avoid some possible problems in the future. It can also clarify the status of the object of sale and purchase, to avoid errors in the deed of sale of land made by PPAT, to create suitability of the contents of the deed of sale and purchase of land with legal deed taking place. These principles will maintain the dignity of the PPAT position and support the quality of work in making the deed and public services. Abstrak: Pejabat Pembuat Akta Tanah (PPAT) seringkali diminta melakukan pengurusan peralihan hak atas tanah Letter C. Sebagai pejabat yang membuat akta autentik, PPAT harus memiliki sikap kehati-hatian dan ketelitian yang baik agar akta yang dibuat dapat memberikan jaminan hak atas tanah bagi masyarakat. Dalam pengurusan peralihan hak atas tanah Letter C, PPAT perlu menerapkan prinsip kehati-hatian agar tidak terjadi permasalahan di kemudian hari. PPAT harus memperhatikan pengurusan di kelurahan/desa terkait dengan pengecekan obyek Letter C, dokumen terkait dengan objek, identitas para pihak, dan permohonan izin. PPAT juga perlu berhati-hati dalam pengurusan di Badan Pertanahan Nasional. Prinsip kehati-hatian perlu diterapkan dalam rangka menghindarkan PPAT dari permasalahan yang mungkin terjadi di kemudian hari, memperjelas status obyek jual beli, menghindarkan kesalahan dalam akta jual beli tanah yang dibuat oleh PPAT, dan menciptakan kesesuaian isi akta jual beli tanah dengan perbuatan hukum yang terjadi. Dengan prinsip kehati-hatian akan menjaga harkat dan martabat jabatan PPAT serta mendukung kualitas kerja dalam pembuatan akta dan pelayanan masyarakat.